The role of SMEs in national economies in East Asia - Harvie, Charles, 1954-; Lee, Boon-Chye (Studies of small and medium size enterprises in East Asia series, 2002)
This volume presents detailed analyses of the role and significance of Small and Medium sized Enterprises (SMEs) in the economies of East Asia. Various aspects of SME operations are studied.